The development of peer reflective supervision amongst nurse educator colleagues: An action research project. (October 2016) - Bulman, C.; Forde-Johnson, C.; Griffiths, A.; Hallworth, S.; Kerry, A.; Khan, S.; Mills, K.; Sharp, P.
Abstract: This action research study developed the use of peer reflective supervision (PRS) amongst eight nurse educators contributing to an undergraduate Adult Nursing programme at a UK University. During the academic year (2013–14), nurse educator co-researchers met for an introductory workshop and then met regularly in pairs to facilitate each other's reflection. This provided an opportunity for nurse educators to reflect on identified issues linked to their role with a facilitative peer. Educators met three additional times in a Reflexive Learning Group (RLG), to gather data on their use of PRS. Audio-recordings from the RLGs were transcribed and analysed using Norton's (2009) thematic analysis framework. Co-researchers iteratively validated the data and an external validation group critically viewed the evidence. Overall, seven themes were generated from the three research cycles. These were: PRS as a Valuable Affirming Experience; Time Issues; Facilitation- Support, Trust and Challenge; Developing a Flexible 'Toolbox'; To Write or Not to Write; Drawing on Literature; and Requirement for Action. Findings add new evidence regarding use of a flexible toolbox of resources to develop reflection and offer practical guidance on the development of PRS. Nurse educators often experienced similar concerns, and a facilitative supervision structure allowed co-researchers to positively explore these. Recognition of work pressures and requirement for time and space for reflection was highlighted, particularly regarding writing, and exploring the literature, to develop critical analysis of experiences. The importance of action as part of the reflective process was emphasised. Co-researchers reported positive personal change as well as the opportunity to highlight issues through their reflection for further action within the organisation. The study adds constructive evidence for the use of reflection to explore professional work, make sense of experiences and develop positive action. It has transferability to a wider international audience interested in the development of reflection amongst colleagues and the use of insider research techniques to challenge and develop practice. Highlights: Use of reflection to explore nurse educator work experiences and develop action. Practical guidance on peer reflective supervision development. Including-time issues, resources to develop reflection, writing, using literature.